2015
DOI: 10.1159/000381351
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Repetitive Transcranial Magnetic Stimulation on Cognitive Performance in Treatment-Resistant Depression. A Systematic Review

Abstract: Background: Major depressive disorder (MDD) is a disabling illness associated with significant functional and psychosocial impairment. Although many psychopharmacological agents are currently available for its treatment, many MDD patients suffer from treatment-resistant depression (TRD). Methods: A systematic review of the current literature (Pubmed/Medline, Scopus and ScienceDirect search) has been conducted with the primary aim to investigate the role of repetitive transcranial magnetic stimulation (rTMS) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 57 publications
3
56
0
1
Order By: Relevance
“…We conducted a literature search in the following databases: PubMed/MEDLINE, EMBASE (Ovid), and PsychINFO (Ovid). In addition, the published systematic review bibliographies of the cognitive effects of rTMS were searched for additional studies (Guse, Falkai, & Wobrock, 2010;Serafini et al, 2015). The search terms included "repetitive transcranial magnetic stimulation" or "rTMS," and "neurocognition" or "neurocognitive performance" or "cognitive effects" or "cognitive" or "neuropsychological," and "randomized controlled trial" or "randomized controlled trial" or "controlled clinical trial" or "RCT" or "sham controlled."…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a literature search in the following databases: PubMed/MEDLINE, EMBASE (Ovid), and PsychINFO (Ovid). In addition, the published systematic review bibliographies of the cognitive effects of rTMS were searched for additional studies (Guse, Falkai, & Wobrock, 2010;Serafini et al, 2015). The search terms included "repetitive transcranial magnetic stimulation" or "rTMS," and "neurocognition" or "neurocognitive performance" or "cognitive effects" or "cognitive" or "neuropsychological," and "randomized controlled trial" or "randomized controlled trial" or "controlled clinical trial" or "RCT" or "sham controlled."…”
Section: Methodsmentioning
confidence: 99%
“…These specific search terms were chosen to be broad enough to capture studies of rTMS conducted in clinical populations, regardless of diagnosis or site of stimulation, and specific enough to limit results to randomised controlled trials where cognitive outcomes were examined. Further, the bibliographies of published systematic reviews of the cognitive effects of rTMS were searched for additional studies (i.e., Guse et al 2010; Dougall et al 2015; Serafini et al 2015), and we contacted study authors as needed to attain additional data. Results were limited to studies in humans and those published in English language.…”
Section: Methodsmentioning
confidence: 99%
“…Given that the site of stimulation (i.e., DLPFC) frequently used for therapeutic rTMS is known to subserve multiple higher level cognitive functions including executive function, learning and memory, and working memory, and that repeated daily administration to this same region over several weeks has proven therapeutic effects, the possibility of cognitive enhancement following repeated rTMS administration remains an open question. Recent systematic reviews conducted in both mixed (Guse et al 2010) and depressed samples (Serafini et al, 2015) indeed have suggested that rTMS has promising cognitive enhancing effects.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike ECT, TMS appears to improve cognitive function. 48 On the other hand, the response of depressive symptoms to ECT is presumed to be more general and robust. 49…”
Section: Adverse Effectsmentioning
confidence: 99%